Indonesian EFL Students’ Perception Towards Online Learning: Voices From Freshmen - Rohim, Agil Abdur (Department of English Language Education, UIN Sunan Ampel Surabaya, 2022)
Covid-19 pandemic has inevitably shifted the conventional face-to-face learning in higher education institution to online learning. This study examined the perceptions of Indonesian EFL students, especially freshmen, towards online learning. Employing quantitative descriptive design with 83 respondents, this study focused on 3 aspects; 1) students’ perception, 2) students’ preferences, and 3) advantage and disadvantage of online learning based on students’ experience. The result showed that based on students’ perception 1) online learning is effective (53%, n = 44) to improve English proficiency, and somewhat effective (42.2%, n = 35) to improve social competences, 2) even though students’ enjoyment shows positive trends, they still prefer face-to-face learning (62.7%, n = 52) rather than online learning (37.3%, n = 31), and 3) the most frequent choose advantage of online learning is able to stay at home (79.5%, n = 66), while the most frequent disadvantage is less interaction with lecturers and classmates (74.7%, n = 62). This research has proven that the implementation of online learning earned numerous positive perceptions, followed with several challenges that need to be overcome by any means.